The economy principle: 17 characteristics that make the English language economical…in comparison to Portuguese – a pedagogical perspective - Fanha Martins, Hélder (2017)
ABSTRACT We believe that all languages in the world use the Economy Principle in some way or other. The principle states that “languages tend to express ideas as economically as possible”. This means that the speaker tends to leave out unnecessary words and not to repeat concepts that have been previously expressed. In the Portuguese language, such expressions as “recuar para trás”, “ambos os dois”, and “preferir antes” are justifiably viewed as poor, since they unnecessarily repeat ideas (“para trás” is implied in “recuar”, “ambos” includes the idea of “os dois”, “preferir” encompasses the concept of “antes”). This type of expressions is anti-economical, and grammar books classify them as pleonasms, i.e. redundancies. English is so easy to learn by foreigners partly because it is one of the languages that most efficiently use the economy principle. In this brief note, we present several perspectives that justify the previous statements, with examples from English and Portuguese.